A rare morphology of the cardiac fibroma in a child: a case report - Tian, Yunfei; Lin, Jiayi; Yang, Xiaohui; Zeng, Debin; Hu, Yuan; Chen, Jingnan; Wu, Zhongshi; Deng, Xicheng (Frontiers in Cardiovascular Medicine, 2024)
Here we report a rare morphology of a cardiac fibroma in a child. A 2-year and 8-month-old toddler came for "chronic constipation" and was found to have a heart murmur on cardiac auscultation. Further transthoracic echocardiography suggested "a strong echogenic mass in the left ventricular wall, with some part of 'a string of beads' in shape extending into left ventricle outflow tract ", which was atypical for either a tumor, thrombus or vegetation. The child underwent resection of the The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest.